Evaluation of lateral flow devices for identification of infected poultry by testing swab and feather specimens during H5N1 highly pathogenic avian influenza outbreaks in Vietnam - Slomka, Marek J. (Influenza Other Respir Viruses, 2011)
Please cite this paper as: Slomka et al. (2012) Evaluation of lateral flow devices for identification of infected poultry by testing swab and feather specimens during H5N1 highly pathogenic avian influenza outbreaks in Vietnam. Influenza and Other Respiratory Viruses 6(5), 318–327. Background  Evaluation of two commercial lateral flow devices (LFDs) for avian influenza (AI) detection in H5N1 highly pathogenic AI infected poultry in Vietnam. Objectives  Determine sensitivity and specificity of the LFDs relative to a validated highly sensitive H5 RRT PCR. Methods  Swabs (cloacal and tracheal) and feathers were collected from 46 chickens and 48 ducks (282 clinical specimens) and tested by both LFDs and H5 RRT PCR. A subset of 59 chicken and 34 duck specimens was also tested by virus isolation (VI), the ‘gold standard’. Results  Twenty‐six chickens and 15 ducks were shown to be infected by at least one RRT PCR positive clinical specimen per bird. Bird‐level sensitivity for the Anigen LFD was 84·6% for chickens and 53·3% for ducks, and for the Quickvue LFD 65·4% for chickens and 33·3% for ducks. Comparison of the three clinical specimens revealed that chicken feathers were the most sensitive with 84% and 56% sensitivities for Anigen and Quickvue respectively. All 21 RRT PCR positive swabs from ducks were negative by both LFDs. However, duck feather testing gave sensitivities of 53·3% and 33·3% for Anigen and Quickvue respectively. Specificity was 100% for both LFDs in all investigations. Conclusions  Although LFDs were less sensitive than AI RRT PCR and VI, high titre viral shedding in H5N1 highly pathogenic avian influenza (HPAI) infected and diseased chickens is sufficient for a proportion of birds to be identified as AI infected by LFDs. Feathers were the optimal specimen for LFD testing in such diseased HPAI scenarios, particularly for ducks where swab testing by LFDs failed to identify any infected birds. However, specimens should be forwarded to the laboratory for confirmation by more sensitive diagnostic techniques.